Enhancement of care through self-monitoring and tailored feedback via text messaging and their use in the treatment of childhood overweight - Bauer, Stephanie; De Niet, Judith; Timman, Reinier; Kordy, Hans (Patient education and counseling, 2010)
OBJECTIVE: This paper first illustrates the general potential of the short message service (SMS) for symptom and behavior monitoring and the provision of tailored feedback. Second, an SMS-based maintenance treatment (SMSMT) is introduced aimed at enhancing the treatment of childhood overweight. - METHODS: After a 12-week cognitive behavioral group treatment (CBGT), 40 children were assigned to the SMSMT for a period of 36 weeks. Children were asked to send weekly self-monitoring data on eating behavior, exercise behavior, and emotions and received tailored feedback. The adherence to SMSMT and changes in Body Mass Index Standard Deviation Scores (BMI-SDS) during the first and second treatment phase were analysed. - RESULTS: Children (mean age=10.05, SD=1.28) submitted 67% of the weekly SMS that they were expected to send in. During CBGT a significant reduction by 0.20 BMI-SDS was observed. The reduction by 0.07 BMI-SDS during the SMSMT did not reach statistical significance. - CONCLUSION: The results support the feasibility of SMSMT in the treatment of childhood overweight. The efficacy of the intervention needs to be demonstrated in an RCT. - PRACTICE IMPLICATIONS: SMSMT is a promising intervention that may extend the reach of treatment centers for childhood overweight at reasonable cost and effort.
Gesehen am 08.12.2022